Clinicopathological characteristics of oestrogen receptor negative, progesterone receptor positive breast cancers: re-evaluating subsets within this group. Issue 4 (9th September 2016) - Ahmed, Syed Salahuddin; Thike, Aye Aye; Zhang, Kathryn; Lim, Jeffrey Chun Tatt; Tan, Puay Hoon
Abstract : Aims: The presence of oestrogen and progesterone receptors (ER, PR) in breast carcinoma is an important prognostic indicator as well as a predictor of likely response to hormonal treatment. Current ambiguity surrounds ER-negative (–)/PR-positive (+) breast cancer (BC) as to whether this phenotype exists as a distinct entity. The independent predictive value of PR for treatment considerations is also in question, as some investigators believe ER status to be the single most important therapeutic predictive factor in BC. We undertook this study to determine the existence of ER(–)/PR(+) BC and the prognostic effect, if any, of this phenotype. Methods: We investigated 267 archival documented ER(–)/PR(+) BCs diagnosed between January 1994 and July 2009. Histological slides were retrieved and reviewed. Tissue microarrays were constructed by selecting two 1 mm cores of tumour per case. Repeat immunohistochemistry was performed for confirmation of the ER(–)/PR(+) status. Clinicopathological parameters including age, ethnicity, tumour size, histological grade, histological subtype, associated ductal carcinoma in situ, lymphovascular invasion and lymph node status were evaluated. Results: On repeat immunohistochemistry, 92 tumours were confirmed as ER(–)/PR(+) BCs. This phenotype accounted for 1.1% of all BC phenotypes and exhibited different clinicopathological features and survival outcome when compared with other phenotypes. ER(–)/PR(+) tumours showed a trend for an early recurrence and poorer overall survival as compared with the patients with ER(+)/PR(+) tumours and similar to ER(–)/PR(–) tumours. Conclusions: Our findings suggest that ER(–)/PR(+) BCs exist, although rare, with distinct pathological and clinical characteristics from patients with ER(+)/PR(+) BCs.